A nomogram for predicting the risk of cerebral vasospasm after neurosurgical clipping in patients with aneurysmal subarachnoid hemorrhage - Zhou, Yu; Qian, Dongliang; Zhou, Zhou; Li, Bin; Ma, Yong; Chai, Erqing (Frontiers in Neurology, 2024)
Cerebral Vasospasm (CVS) is a common complication that occurs after neurosurgical clipping of intracranial aneurysms in patients with aSAH. This complication can lead to clinical deterioration and a poor prognosis. The aim of this study is to explore the risk factors for CVS in aSAH patients who have undergone neurosurgical clipping, develop a nomogram for CVS, and evaluate its performance.Patients with aSAH who underwent neurosurgical clipping in the Department of Neurosurgery from January 2018 to January 2023 were selected as the subjects of this research. The clinical data of these patients were retrospectively analyzed. Logistic multivariate regression analysis was employed to identify the independent risk factors of CVS. A clinical prediction model in the form of a nomogram for CVS was developed using the R programming language and subsequently evaluated for its performance and quality.A total of 156 patients with aSAH were included in the analysis, comprising 109 patients in the training set and 47 patients in the validation set. In the training cohort, 27 patients (24.77%) developed CVS after neurosurgical clipping, while in the validation cohort, 15 patients (31.91%) experienced CVS. Multivariate regression analysis revealed that age, Hcy, WBC, glucose/potassium ratio, aneurysm location, and Modified Fisher Grade were independent risk factors for CVS. The nomogram exhibited excellent discriminative performance in both the training set (AUC = 0.885) and the validation set (AUC = 0.906).CVS was a prevalent complication following neurosurgical clipping in patients with aSAH, with a highly intricate pathogenesis and pathophysiological course. Early prediction of CVS represented a significant challenge in clinical practice. In this study, age, Hcy, WBC, glucose/potassium ratio, aneurysm location, and Modified Fisher Grade emerged as independent risk factors for CVS. The resulting nomogram demonstrated substantial predictive value.